Minipuberty in Klinefelter syndrome: Current status and future directions - Aksglaede, Lise (Am J Med Genet C Semin Med Genet, 2020)
Klinefelter syndrome is highly underdiagnosed and diagnosis is often delayed. With the introduction of non-invasive prenatal screening, the diagnostic pattern will require an updated description of the clinical and biochemical presentation of infants with Klinefelter syndrome. In the first months of life, the hypothalamic-pituitary-gonadal (HPG)-axis is transiently activated in healthy males during the so-called minipuberty. This period represents a “window of opportunity” for evaluation of the HPG-axis before puberty and without stimulation tests. Infants with Klinefelter syndrome present with a hormonal surge during the minipuberty. However, only a limited number of studies exist, and the results are contradictory. Further studies are needed to clarify whether infants with Klinefelter syndrome present with impaired testosterone production during the minipuberty. The aim of this review is to describe the clinical and biochemical characteristics of the neonate and infant with Klinefelter syndrome with special focus on the minipuberty and to update the clinical recommendations for Klinefelter syndrome during infancy.